Bing-Neel syndrome presenting as isolated CNS lymphoplasmacytic lymphoma: A case report and review of the literature. (January 2020) - Grainger, Brian T.; Issa, Samar
Highlights: Bing-Neel syndrome (BNS) is characterised by infiltration of the CNS by lymphoplasmacytic lymphoma cells. It is traditionally regarded as a complication of pre-existing systemic Waldenström's macroglobulinaemia (WM). We describe a patient with apparently isolated leptomeningeal LPL who did not fulfil criteria for concomitant WM. Response to the BTK inhibitor ibrutinib is also observed, consistent with that reported in other cases of BNS. Abstract: Bing-Neel syndrome (BNS) is characterised by infiltration of the central nervous system by lymphoplasmacytic lymphoma (LPL) cells and is traditionally regarded as a complication of pre-existing systemic Waldenström's macroglobulinaemia (WM). We describe the case of a 49 year old woman with leptomeningeal LPL who did not fulfil diagnostic criteria for concomitant systemic WM at presentation, and who failed to respond to conventional chemotherapy treatment (including high dose methotrexate) but did respond to the oral Bruton tyrosine kinase (BTK) inhibitor ibrutinib. This highlights an important variation in the typical natural history of this rare disease and also further supplements emerging evidence regarding efficacy of ibrutinib in its treatment.